Relationship between mode of delivery and development of urinary incontinence: A possible link is demonstrated - Saadia, Zaheera (International Journal of Health Sciences, 2015)
Background: Urinary incontinence is a major problem faced by many mothers and has been traditionally linked to diverse ways of delivery. However, there is still a lack of clinical data, which can corroborate this notion. Thus, the present study was conducted to evaluate the correlation of urinary incontinence developed in women under different modes of delivery that have been used during childbirth. The study was conducted by considering three ways of delivery such as vaginal, cesarean section and the use of instruments during childbirth. The results were compared in each group in terms of number of women that developed or experienced urinary incontinence with those who have no problem at all or have minor problems. Methods: The study was conducted at Qassim University Clinic, and Maternity and Child Hospital Buraidah from Jan-May 2015 as a descriptive cross sectional study. The objective was to determine the core reasons as to why women tend to develop some urinary incontinence after delivery. First 111 women without urinary incontinence and 100 women with urinary incontinence were asked retrospectively about the number of vaginal deliveries they had underwent. Then another group (111 without urinary incontinence and 100 with urinary continence were asked about the number of instrumental deliveries they had undegone. The same was repeated (111 women without urinary incontinence and 100 with urinary incontinence) for women with cesarean section. Results: Having five or more vaginal births had a significantly (p<0.001) high risk for development of urinary incontinence (n=74, 66.67%) as compared to no urinary incontinence (n=8, 8.0%). In the group who had no cesarean section, there was a significantly (p <0 .001) larger proportion of participants with urinary problems (n = 100, 90.09%) than those without urinary problems (n = 61, 61.0%). For participants who have had an instrumental delivery, there was a significantly (p =0 .014) larger proportion of participants with urinary problems (n = 22, 19.82%) than those without urinary problems (n = 8, 8.0%). However, for participants that have not had an instrumental delivery, there was a significantly larger amount of participants without urinary problems than those with urinary problems (p <0 .001). Conclusion: Women with 5 or more vaginal deliveries as well as instrumental deliveries were more liable to develop urinary incontinence in this study. This may be because vaginal deliveries and instrumental deliveries lead to perineal damage. This is further supported by the results of this study showing that women who never had cesarean section were more likely to report urinary incontinence